Urban development transitions and their implications for poverty reduction and policy planning in Uganda - Paul Isolo Mukwaya; Hannington Sengendo; Shuaib Lwasa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Urbanization is one of the critical global trends shaping the future of humanity. At the same time, it has been argued that full development requires an urbanized environment. This paper attempts to examine and characterize the major phases of urbanization in Uganda and what this means for urban policy planning and poverty reduction in the country. Although the history of urbanization in Uganda is relatively young compared to other East African countries, the rate of urban development is reported to be one of the highest in the world. However, little effort is being made to seize the opportunities and maximize the potential benefits of urban development, as well as reduce its potentially negative consequences. The urban development path of Uganda can be classified into five phases, referred to in this paper as transitions, and these are characterized with planning systems that are partly malfunctioning, partly wobbly and incomplete, and partly non-existent. Pertinent socioeconomic, environmental and political problems that are insurmountable for urban planning and management are a feature of the urban areas in the country. Most importantly, welfare and poverty indicators have not shown marked improvements (in absolute terms) for the urban population over the last 50 years. This paper argues for a strong urban planning policy that takes into account the rate of urbanization being experienced in Uganda today, the failure of which will lead to increasing marginalization of city residents.
Keywords: R0; O10; 330; transitions; urbanization; planning; poverty; Uganda